Functional Crown Lengthening: Biological Width Correction - Regia Aristiyanto; Diatri Nari Ratih (Journal of Indonesian Dental Association, 2020)
Introduction: Functional crown lengthening is one of the most common surgical procedures that facilitating restorative treatment. It was done on teeth with inadequate clinical crowns in the presence of deep and subgingival pathologies. Inadequate clinical crowns defined as tooth with less than 2 mm cervico-incisal of sound. Case Report: The 32 years old female patient complained on broken restoration on upper left anterior tooth since one week ago. He also complained about upper right anterior tooth that turned brown. The tooth had received root canal treatment with direct composite restoration since 3 years ago, but the restoration on tooth 11 and 21 was broken. The remaining crown on tooth 11 and 21 was less than 2 mm. The periapical radiograph examination showed tooth 11 and 21 was non-hermetic obturation. Functional crown lengthening and root canal treatment was performed on teeth 11 and 21, with porcelain crown restoration and fiber post. Conclusion: Functional crown lengthening result affects the quality of post retreatment restoration. The success of functional crown lengthening is marked by no recurrent gingival hyperplasia after functional crown lengthening.